Strategy for praventing delays in returning inpatient medical record files based on the PDCA method - Sitti Rahmawati Sinta; Sri Wahyuni; Ahmad Amiruddin (International Journal of Multidisciplinary Learners, 2024)
Medical records are said to be of good quality if they are accurate, reliable, valid, timely, and complete. Inpatient medical record documents must be returned on time. If medical record documents are not returned according to the established SOP, this is considered a delay. This will affect the quality of health services. The purpose of this study was to determine the factors causing delays in returning inpatient medical record files and to create a strategy to prevent factors causing delays in returning medical record files at Buton District Hospital. To see the delay factors, the researcher used a prevention strategy using the PDCA method. The subjects in this study were 5 people with medical record file objects. The type of research used in this study was qualitative with a descriptive approach using a case study research design. Interviews and observations of medical record officers were used during data collection. The results of the study from February to April still experienced delays in returning medical record files where out of 1200 medical record files that had to be returned to the medical record room, there were 586 files that were late (48.9%), in February 48.2%, in March 47.9%, in April 50.2%. Factors that affect the delay in returning medical record files include the Man factor, which is the delay in nurses and doctors completing medical resumes, Methode is more enforced and orderly SOP, strengthening in the implementation of SOP. Medical record officers must remind nurses more often to be on time in returning medical record files, Preferably a warning letter or billing letter signed directly by the hospital director is given to nurses who are late in returning medical record files based on the applicable SOP.